2022
DOI: 10.3390/ijerph19127252
|View full text |Cite
|
Sign up to set email alerts
|

How to Evaluate Investment Efficiency of Environmental Pollution Control: Evidence from China

Abstract: Clarifying the efficiency of investment in environmental pollution control is conducive to better control of environmental pollution. Based on panel data of 30 provinces and cities in China from 2008 to 2017, this study combines the three-stage super-efficient SBM-DEA model and the Global-Malmquist-Luenberger index to measure the efficiency of investment in environmental pollution control in China and analyze regional differences. The results show that: First, the investment efficiency of environmental polluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Some findings in the literature suggest that China's ETS is a valid tool in stimulating corporate green innovation [49,50], with no significant adverse effects on corporate production or employment [51]. On the one hand, technical innovation is the primary force for enhancing effectiveness of controlling and reducing environmental pollution [52] and increasing corporate social and environmental performance. Additionally, it can promote production efficiency of enterprises [53], thereby optimizing the governance performance of the enterprises.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Some findings in the literature suggest that China's ETS is a valid tool in stimulating corporate green innovation [49,50], with no significant adverse effects on corporate production or employment [51]. On the one hand, technical innovation is the primary force for enhancing effectiveness of controlling and reducing environmental pollution [52] and increasing corporate social and environmental performance. Additionally, it can promote production efficiency of enterprises [53], thereby optimizing the governance performance of the enterprises.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…CO 2 emissions per 10,000 yuan of GDP are used to measure the intensity of carbon emissions, which is more scientific than using carbon dioxide emissions directly 32 , as shown in Eq. ( 6 ).…”
Section: The Intensity Of Carbon Emission Measurementmentioning
confidence: 99%
“…Ma et al (2016) [29] found that environmental regulations increase enterprises' spending on environmental protection. However, Zhao et al (2022) [30] believed that more advanced environmental protection technologies should be learned by increasing R&D investment to enhance the efficiency of environmental protection investment. Therefore, according to the ideas in the existing literature, we identified two factors affecting GFRI corporate environmental investment: R&D expenditure and innovation.…”
Section: Introductionmentioning
confidence: 99%